PERANAN TENAGA KERJA PEREMPUAN PADA UKM DEPOK DALAM MENINGKATKAN PENDAPATAN RUMAH TANGGA - M. B. Nani Ariani; Heni Nastiti (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2016)
Since the crisis of employment in the industrial company / plant confined to absorb surplus labor. The increasing needs of family life and the head of the family income is not enough to make the involvement of women in order to increase revenue.The results showed that the characteristics of an average age of reproductive age 35-45 years (50%), has 2 children (41.18%) and have free time 6 hours (32.35%). The role of age, number of children, time spent working on women's labor income is jointly influenced significantly by 92.40%, meaning that its role is quite high, while partially the most dominant is the allocation of time and long work by 92.54%. Partial effect of age and number of children do not have a significant effect while the allocation of time to work a significant effect on women's earnings power. The role of age, number of children, time allocation and labor income women on family income have a significant effect jointly by 38.40% and amounted to 61.60% due to other factors. From the research results in this study suggested an increased skills for youth with less experience, increase working time, more inspiring for innovative product design, reproduce exhibitions for the introduction of products both within and outside the region.